1994
DOI: 10.1037/0096-1523.20.4.887
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spatial cuing on luminance detectability: Psychophysical and electrophysiological evidence for early selection.

Abstract: Three experiments were conducted to determine whether attention-related changes in luminance detectability reflect a modulation of early sensory processing. Experiments 1 and 2 used peripheral cues to direct attention and found substantial effects of cue validity on target detectability; these effects were consistent with a sensory-level locus of selection but not with certain memory- or decision-level mechanisms. In Experiment 3, event-related brain potentials were recorded in a similar paradigm using central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
406
7
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 462 publications
(482 citation statements)
references
References 78 publications
52
406
7
2
Order By: Relevance
“…Whereas spatial selection was associated with enlarged P1 and N1 components to attendedlocation stimuli, the unattended stimuli within the attended object only elicited an enlarged N1. This is consistent with studies suggesting that the P1 and N1 index separate and dissociable processes involved in attentional selection (Luck et al, 1994). Specifically, it has been proposed that, while the P1 component reflects the suppression of irrelevant inputs, modulation of the N1 indexes a subsequent stage of facilitated processing and discrimination of relevant inputs (reviewed in Hopfinger et al 2004).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Whereas spatial selection was associated with enlarged P1 and N1 components to attendedlocation stimuli, the unattended stimuli within the attended object only elicited an enlarged N1. This is consistent with studies suggesting that the P1 and N1 index separate and dissociable processes involved in attentional selection (Luck et al, 1994). Specifically, it has been proposed that, while the P1 component reflects the suppression of irrelevant inputs, modulation of the N1 indexes a subsequent stage of facilitated processing and discrimination of relevant inputs (reviewed in Hopfinger et al 2004).…”
Section: Discussionsupporting
confidence: 87%
“…These mechanisms are not identical, however, because a P1 amplitude modulation was only found with spatial attention. This is in accord with previous findings that point to different roles for the P1 and N1 components of the visual ERP in spatial attention (Luck et al 1994;Hopfinger et al 2004). Whereas the P1 component appears to index an early stage of processing at which inputs from unattended locations are suppressed, the N1 reflects a subsequent stage of enhanced discriminative processing of attended inputs.…”
Section: Physiological Evidencesupporting
confidence: 93%
See 1 more Smart Citation
“…By contrast, in our study, sharing similarities with the experiment of Barnhardt et al (2008), we found an increase in P1m amplitude when the load level of the task at fixation increased. This finding suggests that, unlike the C1 modulations likely reflecting an early attentional gating process in V1, the apparent reduction of the P1 amplitude under LL potentially translates an active suppression mechanism operating in the extrastriate visual cortex (Luck et al, 1994), and aimed at downplaying the possible interference effect created by the distractor during early sensory stimulus processing. As such, these modulations of the P1m to the peripheral distractors with load would correspond to another, later attentional filtering mechanism relative to the C1 component, the former operating maximally during LL.…”
Section: Two-stage Model Of Attention Selection Influenced By Affectmentioning
confidence: 92%
“…Both clinical groups had smaller P1 and larger N1 amplitudes to baseline stimuli compared to healthy controls. The P1 component indexes the allocation of processing capacity to early visual attention and the suppression of irrelevant information (Luck et al, 1994). P1 amplitude increases with greater attention to stimuli during relatively early, sensory stages (Carretié et al, 2009;Hopfinger & Mangun, 2001).…”
Section: Other Between-group Differencesmentioning
confidence: 99%